An Animal-Assisted Physiotherapy Intervention with a Rehabilitation Dog for Walking and Balance Training: A Case Series of Children Living with Cerebral Palsy. - Caron, Valerie; Oates, Alison; Pinto, Romany; Lanovaz, Joel L; Dell, Colleen A; Oosman, Sarah; Donkers, Sarah J (NeuroRehabilitation, 2025)
Purpose: Physiotherapy (PT) is an essential part of care for improving function and increasing community participation in children with cerebral palsy (CP). Combining animal-assisted intervention (AAI) with PT (AA-PT) offers a unique approach, potentially boosting motivation and participation in ambulatory children with CP. This case series piloted AA-PT integrating a rehabilitation dog for children with CP, to enhance walking and balance training. Methods: Four ambulatory children with CP (7–16 y.o.a, GMFCS I-II, 3 girls, 1 boy) participated in an 8-week individualized AA-PT intervention. Assessments at baseline (0 weeks), pre-intervention (8 weeks), post-intervention (16 weeks), and follow-up (24 weeks) included Kids Mini BESTest, timed up and go (TUG), dual task cost (DTC), and spatiotemporal parameters. The AA-PT included weekly 60-min sessions integrating a rehabilitation dog in walking and balance training. Visual analog scales (VAS) assessed perceived comfort, safety, enjoyment, and confidence while walking with and without the rehabilitation dog. Results: Individual-responder analysis showed improvements in Kids Mini BESTest scores, reduced DTC, and increased walking speed for all. Children reported higher enjoyment, confidence, safety, and comfort when walking with the rehabilitation dog. Conclusion: AA-PT integrating a rehabilitation dog may enhance balance, dual-task cost, walking speed, and confidence in ambulatory children with CP.